Associated Topics || Dr. Math Home || Search Dr. Math

### Solving a 6x6 System of Equations

```
Date: 03/24/98 at 13:55:48
From: Jason Goodspeed
Subject: 6x6 equations

Could you please look at the following equation - is there a Cramer's
rule for a 6x6 equation?

a +  b - 2c +  d + 3e -  f  =    4
2a -  b +  c + 2d +  e - 3f  =   20
a + 3b - 3c -  d + 2e +  f  =  -15
5a + 2b -  c -  d + 2e +  f  =  - 3
-3a -  b + 2c + 3d +  e + 3f  =   16
4a + 3b +  c - 6d - 3e - 2f  =  -27

Our 12th grade class and teachers can't come up with a true answer
for each variable. Most of us came up with a dependent system.
Could you help with a solution to this problem so I could show the
class?
```

```
Date: 03/24/98 at 15:29:39
From: Doctor Rob
Subject: Re: 6x6 equations

Yes, there is a Cramer's Rule for any system of linear equations.

This system of equations is not dependent. The determinant of the
matrix of coefficients (the denominator in Cramer's Rule) is -852.
If the system were dependent, the determinant would be zero.

Here is a solution which does not use Cramer's Rule. I hate
evaluating large determinants. This method is called Gaussian
Elimination, or Row Reduction.

You can eliminate "a"s from all equations but the first by subtracting

2 times the first equation from the second,
1 times the first equation from the third,
5 times the first equation from the fourth,
-3 times the first equation from the fifth, and
4 times the first equation from the sixth.

This gives you the following five equations in five unknowns
b, c, d, e, and f:

a + 1*b - 2*c +  1*d +  3*e - 1*f  =   4
-3*b + 5*c        -  5*e - 1*f  =  12
2*b - 1*c -  2*d -  1*e + 2*f  = -19
-3*b + 9*c -  6*d - 13*e + 6*f  = -23
2*b - 4*c +  6*d - 10*e + 0*f  =  28
-1*b + 9*b - 10*d - 15*e + 2*f  = -43

You can divide the fourth of these equations by 2, to get

b - 2*c +  3*d -  5*e + 0*f  =  14

and rearrange the equations to make this the second one:

a + 1*b - 2*c +  1*d +  3*e - 1*f  =   4
b - 2*c +  3*d -  5*e + 0*f  =  14
-3*b + 5*c        -  5*e - 1*f  =  12
2*b - 1*c -  2*d -  1*e + 2*f  = -19
-3*b + 9*c -  6*d - 13*e + 6*f  = -23
-1*b + 9*c - 10*d - 15*e + 2*f  = -43

Now you can eliminate b from all equations but the second one by
subtracting multiples of the second equation from all the rest.
This gives:

a       + 0*c -  2*d -  2*e - 1*f  = -10
b   - 2*c +  3*d -  5*e + 0*f  =  14
3*c -  8*d - 11*e + 2*f  = -47
3*c +  3*d +  2*e + 6*f  =  19
-1*c +  9*d + 10*e - 1*f  =  54
7*c -  7*d - 10*e + 2*f  = -29

Now divide the fifth of these equations by -1, and move it to the
third row, to get

a       + 0*c -  2*d -  2*e - 1*f  = -10
b   - 2*c +  3*d -  5*e + 0*f  =  14
c -  9*d - 10*e + 1*f  = -54
3*c -  8*d - 11*e + 2*f  = -47
3*c +  3*d +  2*e + 6*f  =  19
7*c -  7*d - 10*e + 2*f  = -29

Now you can eliminate c from all equations but the third one by
subtracting multiples of the third equation from all the rest.
This gives:

a               -2*d -  2*e - 1*f  = -10
b          -15*d - 15*e + 2*f  = -94
c      - 9*d - 10*e + 1*f  = -54
19*d + 19*e - 1*f  = 115
30*d + 32*e + 3*f  = 181
56*d + 60*e - 5*f  = 349

Now if we subtract three times the fourth row from the sixth, we get

-1*d +  3*e - 2*f  =   4

which we multiply by -1 and move to the fourth position:

a               -2*d -  2*e - 1*f  = -10
b          -15*d - 15*e + 2*f  = -94
c      - 9*d - 10*e + 1*f  = -54
d -  3*e + 2*f  =  -4
19*d + 19*e - 1*f  = 115
30*d + 32*e + 3*f  = 181

Now we can eliminate d from all equations but the fourth by
subtracting multiples of the fourth from all the other rows.
This gives:

a                    -  8*e +  3*f =  -18
b                - 60*e + 32*f = -154
c            - 37*e + 19*f =  -90
d        -  3*e +  2*f =   -4
76*e - 39*f =  191
122*e - 57*f =  301

Now subtract twice the fifth equation from the sixth:

-30*e + 21*f =  -81

Now divide this by -3:

10*e -  7*f =   27

Subtract 7 times this equation from the fifth:

6*e + 10*f =    2

Now divide this by 2:

3*e +  5*f =    1

Now subtract 3 times this from the equation preceding it by two, to
get:

e - 22*f =   24

Now the system of equations looks like:

a                    -  8*e +  3*f =  -18
b                - 60*e + 32*f = -154
c            - 37*e + 19*f =  -90
d        -  3*e +  2*f =   -4
e - 22*f =   24
3*e +  5*f =    1

Now we can eliminate e from all equations but the fifth by subtracting
multiples of the fifth equation from each of them:

a                         -  173*f =  174
b                     - 1288*f = 1286
c                 -  795*f =  798
d             -   64*f =   68
e         -   22*f =   24
71*f =  -71

Now divide the last equation by 71. Eliminate f from all equations but
the last one by subtracting multiplies of the last equation from each
of the others:

a                                  =  1
b                              = -2
c                          =  3
d                      =  4
e                  =  2
f              = -1

There is your solution. You can check it. Notice that the absolute
values of the numbers we divided by were 2, 3, 2, and 71, whose
product is 852. Where have we seen that number before?

-Doctor Rob,  The Math Forum
Check out our Web site http://mathforum.org/dr.math/
```

```
Date: 03/24/98 at 16:16:32
From: Blane and Meg Goodspeed
Subject: Re: 6x6 equations

Thanks. Your help was greatly appreciated.   Jason
```
Associated Topics:
High School Linear Algebra

Search the Dr. Math Library:

 Find items containing (put spaces between keywords):   Click only once for faster results: [ Choose "whole words" when searching for a word like age.] all keywords, in any order at least one, that exact phrase parts of words whole words

Submit your own question to Dr. Math
Math Forum Home || Math Library || Quick Reference || Math Forum Search